MASLAHAT DALAM PERSPEKTIF AL-QUR`AN DAN SUNNAH - Abbas, Abbas (DIKTUM: Jurnal Syariah dan Hukum, 2015)
There are three main discussions in this article, namely: the nature of beneficiaries, beneficiaries concept in Al-Qurâan and Hadist explanation. Basically, beneficiaries related to human interests. The beneficiaries are something which is regarded by the common sense because of the good and avoiding damage to humans. When a clash between some benefits occurs, it is something that is a matter of high priority is the beneficiaries. In the Qurâan and Sunnah, there are a lot of information about the purpose and wisdom establishment of syaraâ law either globally or in detail.